Diffusion‐weighted imaging (DWI) with apparent diffusion coefficient (ADC) mapping as a quantitative imaging biomarker for prediction of immunohistochemical receptor status, proliferation rate, and molecular subtypes of breast cancer. Issue 3 (27th February 2019) - Horvat, Joao V.; Bernard‐Davila, Blanca; Helbich, Thomas H.; Zhang, Michelle; Morris, Elizabeth A.; Thakur, Sunitha B.; Ochoa‐Albiztegui, R. Elena; Leithner, Doris; Marino, Maria A.; Baltzer, Pascal A.; Clauser, Paola; Kapetas, Panagiotis; et al.
Abstract : Background: Diffusion‐weighted imaging (DWI) with apparent diffusion coefficient (ADC) mapping is one of the most useful additional MRI parameters to improve diagnostic accuracy and is now often used in a multiparameric imaging setting for breast tumor detection and characterization. Purpose: To evaluate whether different ADC metrics can also be used for prediction of receptor status, proliferation rate, and molecular subtype in invasive breast cancer. Study Type: Retrospective. Subjects: In all, 107 patients with invasive breast cancer met the inclusion criteria (mean age 57 years, range 32–87) and underwent multiparametric breast MRI. Field Strength/Sequence: 3 T, readout‐segmented echo planar imaging (rsEPI) with IR fat suppression, dynamic contrast‐enhanced (DCE) T1 ‐weighted imaging, T2 ‐weighted turbo‐spin echo (TSE) with fatsat. Assessment: Two readers independently drew a region of interest on ADC maps on the whole tumor (WTu), and on its darkest part (DpTu). Minimum, mean, and maximum ADC values of both WTu and DpTu were compared for receptor status, proliferation rate, and molecular subtypes. Statistical Tests: Wilcoxon rank sum, Mann–Whitney U ‐tests for associations between radiologic features and histopathology; histogram and q‐q plots, Shapiro–Wilk's test to assess normality, concordance correlation coefficient for precision and accuracy; receiver operating characteristics curve analysis. Results: Estrogen receptor (ER) and progesterone receptor (PR) status had significantly different ADC values for both readers. Maximum WTu ( P  = 0.0004 and 0.0005) and mean WTu ( P  = 0.0101 and 0.0136) were significantly lower for ER‐positive tumors, while PR‐positive tumors had significantly lower maximum WTu values ( P  = 0.0089 and 0.0047). Maximum WTu ADC was the only metric that was significantly different for molecular subtypes for both readers ( P  = 0.0100 and 0.0132) and enabled differentiation of luminal tumors from nonluminal ( P  = 0.0068 and 0.0069) with an area under the curve of 0.685 for both readers. Data Conclusion: Maximum WTu ADC values may be used to differentiate luminal from other molecular subtypes of breast cancer. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;50:836–846.